(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2014)
Objective: Children with Down syndrome (DS) show a delay in cognitive and motor development and have various concomitant health problems. We compared Health-Related Quality of Life (HRQoL) in preschool children with DS with a reference group, and investigated child-related factors (i.e., developmental quotient, adaptive function, health problems, problem behaviour), and maternal level of education on HRQoL. Method: In a cohort of 55 children with DS, HRQoL was measured with the TNO-AZL preschool children Quality of Life Questionnaire (TAPQoL). Data from a reference group were used for comparison. Developmental Quotient (DQ) was assessed with the Bayley Scales of Infant Development II, adaptive function with the Pediatric Evaluation of Disability Inventory, health problems were derived from the medical file, and behavioural problems were measured with the Child Behaviour Checklist. Results: Children with DS (N=55; mean age 41.7 months) scored significantly lower on the TAPQoL domains lung and stomach problems, motor function and communication compared to the reference group. DQ had a significant negative correlation with the domains lung problems and liveliness. Children with DS with respiratory or gastro-intestinal problems showed significant lower scores on lung problems and communication. Problem behavior had a significant negative correlation with the domains sleeping, appetite and social function. A low level of maternal education correlated negatively with positive mood. Adaptive function and congenital heart defect (CHD) did not significantly correlate with HRQoL. Conclusion: Preschool children with DS show a lower HRQoL on particular domains of functioning compared to a normative sample. HRQoL of children with DS is correlated to DQ, respiratory and gastro-intestinal health problems, problem behaviour and maternal education, but not to CHD and adaptive function.